Application of social environmental accounting in village-owned business enterprises to realize green accounting - Hariniati Wida; Mardiani Lisna; Nabila Luthfi (BIO Web of Conferences)
Village-Owned Enterprises (BUMDes) aims to improve village welfare by optimizing village resources. BUMDes are expected to carry out social responsibilities towards the community during their operations, including implementing environmental accounting. In environmental accounting, management informs stakeholders about their responsibilities and how an entity’s business actions impact the environment. The term “environmental accounting” refers to accounting as a source of this information. The financial report in Green Accounting conveys information about the environmental impact. The aim of this research is to analyze the implementation of Green Accounting in BUMDes “Bagjaraharja” in relation to the existence of Green Accounting as a benchmark for the realization of the Green Accounting entity. This qualitative descriptive study involves in-depth interviews with related parties, environmental accounting observations, examination of BUMDes financial reports, and documentation of the results. After observations, interviews and documentation were carried out, data was collected, and conclusions were made. BUMDes “Bagjaraharja” has prepared a report on environmental impacts in accordance with PSAK 1 concerning the presentation of financial statements. Even though this report is still simple, the unique presentation of this environmental accounting report shows the attention of BUMDes “Bagjaraharja” to the provision of environmental accounting information. Ultimately, the policies, human resources and infrastructure readiness of the implementing entity are very important to optimize the implementation of environmental accounting.